Discovery and structure-activity relationships study of positive allosteric modulators of the M3 muscarinic acetylcholine receptor. Issue 13 (1st July 2020) - Tanaka, Hiroaki; Negoro, Kenji; Koike, Takanori; Tsukamoto, Issei; Yokoyama, Kazuhiro; Maeda, Jun; Inagaki, Yusuke; Shimoshige, Yukinori; Ino, Katsutoshi; Ishizu, Kenichiro; Takahashi, Taisuke
Graphical abstract: Abstract: The M3 muscarinic acetylcholine receptor (mAChR) is a member of the family of mAChRs, which are associated with a variety of physiological functions including the contraction of various smooth muscle tissues, stimulation of glandular secretion, and regulation of a range of cholinergic processes in the central nerve system. We report here the discovery and a comprehensive structure-activity relationships (SARs) study of novel positive allosteric modulators (PAMs) of the M3 mAChR through a high throughput screening (HTS) campaign. Compound 9 exhibited potent in vitro PAM activity towards the M3 mAChR and significant enhancement of muscle contraction in a concentration-dependent manner when applied to isolated smooth muscle strips of rat bladder. Compound 9 also showed excellent subtype selectivity over other subtypes of mAChRs including M1, M2, and M4 mAChRs, and moderate selectivity over the M5 mAChR, indicating that compound 9 is an M3 -preferring M3 /M5 dual PAM. Moreover, compound 9 displayed acceptable pharmacokinetics profiles after oral dosing to rats. These results suggest that compound 9 may be a promising chemical probe for the M3 mAChR for further investigation of its pharmacological function both in vitro and in vivo .